2015
DOI: 10.1074/jbc.m114.631820
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role for γ-Catenin in the Regulation of Cancer Cell Migration via the Induction of Hepatocyte Growth Factor Activator Inhibitor Type 1 (HAI-1)

Abstract: Background: γ-Catenin is a tumor suppressor in lung cancer.Results: γ-Catenin is a novel regulator of HAI-1 and cell migration.Conclusion: γ-Catenin and HAI-1 regulate cell migration and sensitize NSCLC cells to c-MET inhibitor.Significance: Targeting γ-catenin-mediated HAI-1 expression might be a new strategy to treat lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 34 publications
0
24
1
Order By: Relevance
“…PG, also known as γ‐catenin,31, 32 is a component of adherens junctions and desmosomes, and it plays an important role in Wnt/β‐catenin signaling 33, 34. In several tumors, the loss of PG expression by cells has been related to tumor growth, invasive behavior and hence metastatic progression 35, 36.…”
Section: Discussionmentioning
confidence: 99%
“…PG, also known as γ‐catenin,31, 32 is a component of adherens junctions and desmosomes, and it plays an important role in Wnt/β‐catenin signaling 33, 34. In several tumors, the loss of PG expression by cells has been related to tumor growth, invasive behavior and hence metastatic progression 35, 36.…”
Section: Discussionmentioning
confidence: 99%
“…Most evidence shows that reduced levels of HAI‐1/SPINT1 in carcinoma cells lead to enhanced invasiveness and metastasis (Fig. d) . In fact, relationship between the reduced HAI‐1/SPINT1 and a poorer clinical outcome of gynecological, mammary, prostatic, oral and pancreatic ductal carcinomas have been reported .…”
Section: Hai‐1/spint1 Suppresses the Epithelial To Mesenchymal Transimentioning
confidence: 98%
“…Furthermore, plakoglobin expression in plakoglobin‐deficient and mp53‐expressing cells reduced growth, migration and invasion of these cells in vitro . Plakoglobin has also been shown to regulate the expression of HAI‐1 and to reduce migration in a p53‐dependent way in NSCLC cells . Coimmunoprecipitation experiments indicated that plakoglobin interacted with p53.…”
Section: Discussionmentioning
confidence: 98%
“…Plakoglobin is an armadillo protein family member and is a paralog of β‐catenin with similar dual cell‐cell adhesion and signaling activities . However, unlike β‐catenin that acts as an oncogene through its interaction with the transcription factors T‐cell factor/lymphoid enhancer‐binding factor (TCF/LEF), and activation of Wnt signaling pathway, plakoglobin generally acts as a tumor/metastasis suppressor . We have shown that plakoglobin can act as a tumor/metastasis suppressor by at least 3 mechanisms: regulation of stability and subcellular localization of growth regulating molecules, interaction with transcription factors involved in the regulation of cell growth and metastasis and sequestration of β‐catenin oncogenic activities; see also …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation